COMMUNITY-BASED SOCIAL PROTECTION PROGRAMMES AND HOUSEHOLD WELLBEING IN THE NIGER DELTA REGION - Amakiri Jackson Fred; Ebikeiseye Patimi (PT. Antis International Publisher, 2026)
Objective: This study investigates the relationship between community-based social protection programmes and household well-being in the Niger Delta Region. Specifically, the study focused on key community-based social protection programmes such as the availability of community welfare programs, receipt of educational support, access to emergency relief funds, and micro-insurance schemes on household well-being. Method: The population of the study consists of 32,277,901 people across the nine Niger Delta states, namely Abia, Rivers, Akwa Ibom, Bayelsa, Delta, Cross River, Edo, Imo, and Ondo, as obtained from the National Population Commission. The sample size was determined using the Taro-Yamane method. Data were collected through a self-structured instrument titled “Community-Based Social Protection Programmes and Household Well-being Questionnaire (CBSPPHWBQ)”. Percentage and frequency counts were used to address the research questions, while the chi-square statistical technique, with the aid of Statistical Package for the Social Sciences version 26, was used to test the hypotheses. Results: The results of the study revealed that the availability of community welfare programs, Receipt of educational support, Access to emergency relief funds, and Micro-insurance schemes have a positive and significant relationship with household well-being in the Niger Delta region. It was concluded that community-based social protection programmes had a substantial impact on household welfare in the Niger Delta region. Novelty: It was therefore recommended amongst others that the Niger Delta Development Commission, local government councils, and community-based organizations should strengthen the implementation of community welfare programmes by increasing investments in social infrastructure, healthcare facilities, potable water supply, and community support services.